Development of automatic power factor correction system by using PIC microcontroller through simulation study - Atifa Faaidha, Munauwer (Universiti Malaysia Perlis (UniMAP), 2019)
This thesis presents the design and analysis of an automatic power factor correction system using PIC microcontroller for single phase low voltage distribution system (230V/50Hz). Power factor plays a great role in an electrical system. A low power factor will draw more current in the system and this will lead to high electricity bills and higher power loses. Conventional way to improve power factor is by installing a static capacitor bank which is connected permanently to the electrical system through fused switches. However, this method is not effective as the load is usually fluctuating according to demand. Hence, the operation and power factor correction is not optimized as the capacitive compensation does not change according to load variations. Therefore, a system that will adjust the power factor automatically according to load fluctuations is needed. So, in this project an automatic power factor system will be designed and developed in order to solve this problem. The designed system is basically used a PIC 18F452 microcontroller to calculate and control power factor in an electrical system by automatically connect or disconnect capacitor banks according to load changes. The designed system has been tested in Proteus development software.